Transformer Explosion and Impact on the Reinforced Blast Wall - Mazlan, Abu Seman; Feng, Yun Tian; Zainorizuan, Mohd Jaini; Nasly, Mohamed Ali (Penerbit UMP, 2012)
Transformer is one of the vital equipment to provide stable and reliable electricity to the community. The transformer is quiet while in operation, therefore it is hardly to realise if placed inside the building. The price for one transformer can be up to few millions Malaysian Ringgit. The worst of the transformer explosion may lead to the major blackout. Transformer explosion may due to, lack of maintenance or the problems inside itself whilst in operation. In the past at substation, the transformers were placed adjacent to each other and without a wall in between. Nowadays, installing walls between transformers have become in practice to protect other transformers in the events of explosion. In Malaysia, a reinforced blast wall is built as the protection. The finite element method (FEM) is employed for the simulation of the potential damage of reinforced blast wall. A FEM software is used due to the capability of analysing and simulating reinforced concrete structures subjected to high rate and short duration dynamic loading in the previous research works. The simulation results clearly reveal, after the impact load is applied, the cracks start to occur at certain time instants at the bottom of the wall on the transformer side. This follows later with the cracks on the other side at about one third of the wall height. The propagations of the crack then continue to move downwards in the curvy shape. The previous work and the field test provide indirect evidence that the structural behaviour and the cracks patterns are comprehended.